An organic zinc-chelating-peptide GQ-Zn supplementation ameliorates diarrhea through regulate gut microbiota and metabolites in pre-weaning Holstein calves - Linhai Yang; Zihai Wei; Yanjing Su; Xianghuang Wang; Yufeng Du; Muhammad Zahid Farooq; Jianxiong Li; Qingbiao Xu (Animal Nutriomics)
Newborn calf diarrhea has led to widespread overuse of antibiotics. Therefore, it is crucial to find effective solutions for calf diarrhea. In this study, we aimed to evaluate the impact of the synthetic organic zinc-chelating-peptide glycine-glutamine-Zn (GQ-Zn) on the microbiota and metabolites in the gut of calves with diarrhea. The results showed that GQ-Zn alleviated diarrhea in calves. Additionally, 16S rDNA sequencing and metabolomic analysis revealed that GQ-Zn improved antioxidant capacity, relieved inflammation, altered the gut microbiota by decreasing the number of harmful bacteria Prevotella denticola, Fusobacterium necrophorum and influenced metabolomic profiles via the linoleic acid metabolic pathway in calves. In conclusion, GQ-Zn supplementation alleviated diarrhea through regulating the gut microbiota and metabolites in pre-weaning Holstein calves.